2017
DOI: 10.1007/s00415-017-8573-1
|View full text |Cite
|
Sign up to set email alerts
|

Mortality after primary intracerebral hemorrhage in relation to post-stroke seizures

Abstract: Seizures after intracerebral hemorrhage are repeatedly seen. Whether the development of seizures after intracerebral hemorrhage affects survival in the long term is unknown. This study aims to determine the relation between seizures (i.e., with and without anti-epileptic therapy) and long-term mortality risk in a large patient population with intracerebral hemorrhage. We retrospectively included patients with a non-traumatic ICH in all three hospitals in the South Limburg region in the Netherlands between Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 26 publications
1
26
2
Order By: Relevance
“…As reported above, this study is limited because it enrolled only patients aged 18 to 50 years [25]. On the contrary, Claessens et al observed that seizures after ICH were not significantly related to mortality risk after follow-up up to 10 years [23]. Our results agree with this last survey.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As reported above, this study is limited because it enrolled only patients aged 18 to 50 years [25]. On the contrary, Claessens et al observed that seizures after ICH were not significantly related to mortality risk after follow-up up to 10 years [23]. Our results agree with this last survey.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, Claessens et al conducted a retrospective study to explore a possible association between post-stroke seizures and long-term mortality. After correction for possible confounding variables, the authors concluded that seizures were not significantly related to mortality risk [23]. Conversely, in the prospective Future study, Arntz et al showed that post-stroke seizures negatively affect long-term disability and mortality [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Our 10-year survival rate was very similar to the one reported in a population-based study that enrolled 7-day ICH survivors (38% vs. 37%, respectively). 21 In another population-based study with significant methodological differences, 10-year survival rate was slightly lower (24.1%). 22 Only one population-based study that collected data of 28-day ICH survivors of (enrolment period 1985–1991) reported a follow-up data longer than 10 years.…”
Section: Discussionmentioning
confidence: 92%
“…Consequently, Jo et al reported that nanoscale iron injection into the adult mouse cortex leads to a reduction in the number of GABAergic interneurons [ 6 ]. The rate of seizures after intracranial hemorrhage has been reported to be around 10–15% for intracerebral hemorrhage and 10–20% for subarachnoid hemorrhage, respectively [ 1 , 4 , 5 ]. In cases of traumatic brain injury, mechanisms including neuroinflammation, tauopathy, and mediation by toll-like receptors are discussed to cause seizures in 10–20% of patients [ 10 ].…”
Section: Discussionmentioning
confidence: 99%